Sociolinguistic Aspects of the Ashkenazim Language Situation in the Russian Empire at the Turn of the 19th and in the Early 20th Centuries (On the Base of Sholom Aleichem's Writings) - Boichuk, Igor V.; Eschenko, Irina О.; Kamyshanchenko, Elena А.; Taranova, Elena N.; Genkin, Yuliana Y. (Journal of History Culture and Art Research, 2017)
The paper deals with the sociolinguistic situation of the Ashkenazi Jews in the Russian Empire at the end of the 19th century and in the early 20th century. The research is based on the works of a leading Yiddish author and playwright - Sholom (Sholem) Aleichem. His writings, besides their highest artistic value, have been found to be a relevant source of sociolinguistic information. A sociolinguistic analysis of the Ashkenazim language situation has been carried out. The main languages spoken by the Ashkenazim in the Pale of Settlement have been singled out. Their interrelation has been established. Each language played a special role in the life of the Ashkenazim at the period: Hebrew enjoyed high social prestige and alongside with Aramaic was mainly the language of religion. Yiddish was the vernacular of the Ashkenazim in the Pale of Settlement, and it had to struggle for achieving its status as a literary language. Russian, Ukrainian and Moldavian were mainly used for communication with the surrounding Gentiles. Polish remained as a fading vestige of former Polish presence in the area. German and French were the most common foreign languages.